Cultural construction of Quranic politics - Mansour Mirahmadi (رهیافتهای سیاسی و بین المللی)
Cultural construction of Quranic politics Understanding Quranic politics requires understanding the cultural construction of the Holy Quran. Using the method of thematic interpretation, the present article tries to study the concept of Qur'anic politics within this cultural construction in the framework of a semantic approach. The study conducted in this article shows that "Allah" as the focal word, puts the value of theism in the focal position, forming a system of value concepts around it. These concepts form the cultural construction of the Holy Quran. Placing politics within such a cultural construction reveals the place of politics in the Holy Qur'an. Politics, as a public activity governing authority and governance, is endorsed by the Holy Qur'an when it is embedded in a God-centered cultural construction. This cultural construction is composed of value concepts such as righteousness , responsibility, sustainability, justice, commitment and improvement. Keywords: "semantic approach", "cultural construction", "Quranic politics", "governance", "theism".